Intervertebral Disc Degeneration: Multifactorial Disease and Treatment of Pain with Adipose-Derived Stem Cells (International Journal of Scientific Research and Management (IJSRM), 2025)
Abstract Intervertebral Disc Degeneration (IVDD) is one of the most commonly observed causes of chronic low back pain and disability that exist globally. The pathophysiology is complex and multifactorial: inflammation, mechanical stress, cellular senescence, and extracellular matrix degradation. Conventional therapies are largely palliative and symptom-directed rather than aimed at reversing the process of degeneration. However, recent developments in regenerative medicine have provided some hope toward the use of ADSCs, given that they have anti-inflammatory, anti-apoptotic, and matrix-restorative properties. The present paper irreverently explores the IVDD etiology, assesses the mechanistic basis of ADSC-based regeneration, and synthesizes the current preclinical and clinical evidence in support of its efficacy. While dramatic results have been reported, barriers still exist that obstruct the mainstream clinical application of ADSCs, such as delivery challenges and regulatory concerns, as well as long-term safety in use. Herein, a roadmap will be suggested for the overall stem cell-based treatment options in IVDD, which thus would provide a future perspective in regenerative spinal medicine.